2005
DOI: 10.1267/ahc.38.1
|View full text |Cite
|
Sign up to set email alerts
|

Association of Protein Phosphatase 1 Delta with Nucleolin in Osteoblastic Cells and Cleavage of Nucleolin in Apoptosis-induced Osteoblastic Cells

Abstract: Protein phosphorylation and dephosphorylation has been recognized as a key mechanism in cell function. Okadaic acid is a potent inhibitor of PP1 and PP 2A and induces apoptosis in human or mouse cells including osteoblasts. Nucleolin is an abundantly expressed nucleolar phosphoprotein and is located mainly in the nucleolus. The staining pattern of nucleolin in cultured osteoblastic cells is similar to that of PP1d. Nucleolin was demonstrated to bind to PP1d in nucleolus in human osteoblastic cells by using imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…We previously reported that calyculin A or okadaic acid, potent inhibitors of protein phosphatases type 1 and type 2A, induced apoptosis in osteoblastic cells Haneji, 2005) and oral squamous carcinoma cells (Fujita et al, 2004;Okamura et al, 2004). We also obtained evidence PTEN implicating in the initiation and progression of calyculin A-or okadaic acid-induced apoptosis (Okamura et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…We previously reported that calyculin A or okadaic acid, potent inhibitors of protein phosphatases type 1 and type 2A, induced apoptosis in osteoblastic cells Haneji, 2005) and oral squamous carcinoma cells (Fujita et al, 2004;Okamura et al, 2004). We also obtained evidence PTEN implicating in the initiation and progression of calyculin A-or okadaic acid-induced apoptosis (Okamura et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…PTEN (phosphatase and tensin homolog deleted on chromosome ten), also referred to as mutated in multiple advanced cancers (MMAC), was discovered as a tumor suppressor gene (Li et al, 1997;Steck et al, 1997). We previously reported that calyculin A or okadaic acid, potent inhibitors of protein phosphatases type 1 and type 2A, induced apoptosis in osteoblastic cells Haneji, 2005) and oral squamous carcinoma cells (Fujita et al, 2004;Okamura et al, 2004). We also obtained evidence PTEN implicating in the initiation and progression of calyculin A-or okadaic acid-induced apoptosis (Okamura et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Protein phosphatases can dephosphorylate many different substrates in vitro and in vivo (Honkanen and Golden, 2002). They are involved in various aspects of cell regulation, and play important roles in metabolism (Yoshida et al , 2003; Haneji, 2005; Morimoto et al , 2005; Moorhead et al , 2007). Intracellular phosphatases play a central role in signal transduction pathways related to inflammation (Shanley et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is one of the essential steps in the maintenance of normal cell populations of adult mammals and occurs continually in various cell populations. Apoptosis is a morphologically and biochemically distinct mode of cell death that plays major roles during embryogenesis, carcinogenesis, cancer treatment, or immune and toxic cell killing (1)(2)(3)(4)(5). The cytologically apparent stages of apoptosis are rapid condensation of chromatin and fragmentation of the cells with membraneenclosed apoptotic bodies that are phagocytosed and digested by nearby resident cells (6).…”
Section: Introductionmentioning
confidence: 99%